Medical migration and world health. Issue 4 (December 1977) - Fraser, Alan G
Abstract : Everyone knows that British doctors are emigrating and that other doctors, mostly from the third world, are immigrating to Britain. Also everyone thinks that he knows the reasons why. However, the Edinburgh Medical Group thought the various reasons for this medical migration should be examined more closely, and held a symposium (Chairman, Professor A S Duncan, Professor Emeritus of Medical Education in the University of Edinburgh) to examine the causes for medical migration at the present time. Medical teaching and practice is still basically as it has been developed in the West and so overseas doctors trained in Britain take with them not only the medical knowledge and skills but also the attitudes of the West when they return to their own countries. Consequently they wish to settle in the towns and practise as consultants when the real medical problems in many of the developing countries are those of a rural population needing health care rather than treatment in what have been called `disease palaces'. As speakers made clear, a new responsibility must fall on those training doctors from overseas in the British medical schools to fit them not for the dream world of the sophisticated medical scene but for the realities of working in often badly equipped clinics and dealing with common conditions such as malnutrition and other problems of maternity and child health. The symposium also included discussions as to why British doctors wished to emigrate. Money seemed to be the most compelling motive, but opportunities were being limited for their migration for economic and political reasons. Finally, a look at the whole of the medical scene in Britain: perhaps the standard sought in Britain both by the doctor and the patient is too high and too individualistic. Events will show if this be true.